Biomehanika teka - Mušič, Pia (Šport (Ljubljana), 2020)
Due to its accessibility, low cost and well-known health benefits, running has become one of the most popular sports in the world. With its increasing popularity the number of running related injuries, especially in the lower extremities have increased. The most common are plantar fasciitis, Achilles tendinopathy, patellofemoral pain syndrome, iliotibial band syndrome and tibial stress fracture. In this review paper, we explored the novel insights on the field of biomechanical running-related injury risk factors. We focused on individual injuries, rather than injury risk in general. We found out that certain biomechanical risk factors are similar across injuries. For primary prevention purposes, elimination of all running-related injury risk factors seems reasonable, while more attention should perhaps be given to injury-specific risk factors in secondary and tertiary prevention. Based on the literature review, we also found out that sex is an important factor in running-related injury incidence; male runners are more prone to develop Achilles tendinopathy, while female runners more often sustain patellofemoral pain syndrome and iliotibial band syndrome. The main limitation of the research that we reviewed is in the lack evidence regarding causal relationship between biomechanical risk factors and injury occurrence.
Keywords: dejavniki tveganja; kinematics; kinematika; kinetics; kinetika; risk factors; running; running related injuries; sports injuries; športne poškodbe; tek; tekaške poškodbe